Toxicity, outcome, and management of anthracycline overdoses in 16 dogs. (25th November 2021) - Lawson, Haylie C.; Musser, Margaret L.; Regan, Rebecca; Moore, Antony S.; Hohenhaus, Ann; Flesner, Brian; Johannes, Chad M.
Abstract: Background: Despite multiple reports of chemotherapy overdoses (ODs) in human and veterinary medicine, anthracycline ODs have been described infrequently. Hypothesis/Objectives: Describe toxicities, treatments, and overall outcome after anthracycline OD in dogs. Animals: Twelve mitoxantrone (MTX) and 4 doxorubicin (DOX) ODs were evaluated. Methods: Multicenter retrospective analysis. The American College of Veterinary Internal Medicine oncology and internal medicine listservs were solicited for cases in which a chemotherapy OD occurred. Results: Sixteen anthracycline cases were collected. Anthracycline ODs occurred because of an error in chemotherapy preparation (n = 9), or dose miscalculation (n = 7). The overall median OD was 1.9× (range, 1.4‐10×) the prescribed amount. Most ODs were identified immediately after drug administration (n = 11), and the majority of patients were hospitalized on supportive care (n = 11) for an average of 8 days (range, 3‐34 days). Adverse events after the OD included neutropenia (94%), thrombocytopenia (88%), anemia (63%), diarrhea (63%), anorexia (56%), vomiting (38%), lethargy (31%), and nausea (25%). Two patients did not survive the OD. High grade neutropenia was common and did not appear to be mitigated by the administration of filgrastim. Conclusions and Clinical Importance: All patients received supportive care after identifying the OD and death was uncommon. Further evaluation is needed to determine ideal therapeutic guidelines anthracycline OD.